2003
DOI: 10.1016/s0378-7788(02)00240-2
|View full text |Cite
|
Sign up to set email alerts
|

An empirical correlation for the outside convective air-film coefficient for horizontal roofs

Abstract: From measurements of surface heat transfer on the roofs of two commercial buildings in Northern California we have developed a correlation that expresses the outside convective air film coefficient for flat, horizontal roofs as a function of surface-to-air temperature difference, wind speed, wind direction, roof size, and surface roughness. When used in hourly building energy analysis programs, this correlation is expected to give more accurate calculation of roof loads, which are sensitive to outside surface … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(33 citation statements)
references
References 3 publications
0
31
0
Order By: Relevance
“…This agreement suggests that the CHTC is relatively independent of roof size, but is inconsistent with the former remarks based on indoor experiments (e.g., Cole and Sturrock, 1977). In addition, this tendency is also inconsistent with the modelling of the local Nusselt number of a flat roof by Clear et al (2003). The effect of the parapets around the target roofs is a possible factor.…”
Section: Horizontal Roofmentioning
confidence: 59%
“…This agreement suggests that the CHTC is relatively independent of roof size, but is inconsistent with the former remarks based on indoor experiments (e.g., Cole and Sturrock, 1977). In addition, this tendency is also inconsistent with the modelling of the local Nusselt number of a flat roof by Clear et al (2003). The effect of the parapets around the target roofs is a possible factor.…”
Section: Horizontal Roofmentioning
confidence: 59%
“…In [2,[3][4][5][6][7][8][9][10][11][12][13][14][15][16] it is shown that the average CHTC on the windward façade is not very sensitive to wind direction so that a wind direction of 45° from the normal can represent a wide range of wind directions between 0° and 60°.…”
Section: Cfd Numerical Modelmentioning
confidence: 99%
“…The need for more accurate and truthful estimates of CHTCs for buildings led to an extensive amount of field measurements for building facades [15][16][17][18][19][20][21][22][23][24][25][26], for roofs [24,27,28] and to study the effect of glazing framework on the CHTC [29][30][31]. A clear overview of the different experimental techniques to determine these CHTCs and their limitations was given by Hagishima et al [9].…”
Section: Full-scale Experimentsmentioning
confidence: 99%